Cert Prep: Unity Certified Associate Game Developer Audio and Effects. - Thorn, Alan (linkedin.com, 2021)
Learn how to create amazing soundscapes and particle-driven effects for Unity projects, while preparing for the Unity Certified Associate: Game Developer exam.